A Compromised Maxillofacial Wound Healing Model for Characterization of Particulate Bone Grafting: An In Vivo Study in Rabbits - Hussein, Nourhan; Nayak, Vasudev Vivekanand; Dharmaraj, Neeraja; Mirsky, Nicholas A.; Norton, William; Ramagli, Lori; Tailor, Ramesh; Kasper, F. Kurtis; Coelho, Paulo G.; Witek, Lukasz; Young, Simon (Journal of biomedical materials research. Part B, Applied biomaterials, 2025)
Preclinical testing of tissue engineering modalities are commonly performed in a healthy wound bed. These conditions do not represent clinically relevant compromised oral wound environments due to radiation treatments seen clinically. This study aimed to characterize the bone regeneration outcomes in critical‐sized mandibular defects using particulate grafting in an irradiated preclinical model of compromised wound healing. Sixteen New Zealand white rabbits were divided into two groups ( n = 8/group), namely (i) irradiated (experimental) and (ii) non‐irradiated (control). The rabbits in the experimental group received a total of 36 Gy radiation, followed by surgical intervention to create critical‐sized (10 mm), full‐thickness mandibular defects. The control group was subjected to the same surgical intervention. All defects were filled with bovine bone grafting material (Bio‐Oss, Geistlich, Princeton, NJ, USA) and allowed to heal for 8 weeks. At the study endpoint, rabbits were euthanized, and their mandibles were harvested for micro‐computed tomographic, histological, and histomorphometric processing and analysis. Qualitative histological analysis revealed increased levels of bone formation and bridging in the control group relative to the experimental group. This was accompanied by increased levels of soft tissue presence in the experimental group. Volumetric reconstruction showed a significantly higher degree of bone in the control group (27.59% ± 2.71), relative to the experimental group (22.02% ± 2.71) ( p = 0.001). The irradiated rabbit model exhibited decreased bone regeneration capacity relative to the healthy subjects, highlighting its suitability as a robust compromised wound healing environment for further preclinical testing involving growth factors or customized, high‐fidelity 3D printed tissue engineering scaffolds.